1999
DOI: 10.1152/ajpendo.1999.277.4.e693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein intake on plasma and erythrocyte free amino acids and serum IGF-I and IGFBP-1 levels in rats

Abstract: Amino acid (AA) levels in plasma and erythrocytes (RBC) were determined in rats ( n = 29) fed diets with 6, 21, and 35% protein, and their association with insulin-like growth factor I (IGF-I), insulin, or IGF-binding protein (IGFBP)-1 levels was studied. Free AA in plasma and RBC were determined by reversed-phase high-pressure liquid chromotography, and IGF-I, IGFBP-1, and insulin plasma levels were determined by RIA. Rats fed the low-protein (6%) diet were growth-retarded and had lower serum IGF-I levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
5
17
0
Order By: Relevance
“…We did observe some significant differences between knockout and wild-type mice along the tested parameters, but no consistent changes in response to the dietary protein supply could be found. As expected, plasma urea levels increased with increased protein intake [11,19], but independent of genotype. In spite of the significant differences as shown in Table 2, mean values for all parameters and all groups were found to lie within the reference ranges as calculated for control mice on the 20% protein diet.…”
Section: Discussionsupporting
confidence: 80%
“…We did observe some significant differences between knockout and wild-type mice along the tested parameters, but no consistent changes in response to the dietary protein supply could be found. As expected, plasma urea levels increased with increased protein intake [11,19], but independent of genotype. In spite of the significant differences as shown in Table 2, mean values for all parameters and all groups were found to lie within the reference ranges as calculated for control mice on the 20% protein diet.…”
Section: Discussionsupporting
confidence: 80%
“…IPA-core analysis revealed the amino acid metabolism to be the most significantly affected function in the livers of the LP8 group. Additionally, the aggravation of protein nutrition is known to up-regulate the expression of Igfbp1 in liver, which is thought to be a cause of growth retardation (23,24). We have observed in hepatoma cells that addition of a disproportionate amount of a single amino acid to the culture media up-regulates Igfbp1 expression (data not shown), suggesting that the amino acid directly regulates the Igfbp1 gene.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies on nutritional analysis of Hilsha fish showed that it is rich in various essential amino acids (EAA) and non-essential amino acids (NEAA) [26]. EAA-to-NEAA ratio showed a positive correlation to IGF-I and insulin whereas an inverse correlated to IGFBP-1 [27].…”
Section: Discussionmentioning
confidence: 96%
“…Since antique era, plants with medicinal properties are enormously used in treating diabetes throughout the world. Many recent scientific investigations have also confirmed the efficacy of plant preparations, few of which are remarkably effective [11]. Cucurbitaceae is a plant family well known to have about 125 extant genera including 960 species.…”
Section: Introductionmentioning
confidence: 99%